Evaluation of the effect of Loigolactobacillus coryniformis K8 CECT 5711 consumption in health care workers exposed to COVID-19 - Rodriguez-Blanque, Raquel; Sánchez-García, Juan Carlos; Cobos-Vargas, Ángel; Aguilar Quesada, Ana; Maldonado-Lobón, Jose A.; Olivares, Mónica; Blanco-Rojo, Ruth (Frontiers in Nutrition, 2022)
Following the spread of the SARS-CoV-2 coronavirus, an unprecedented burden has been placed on health care systems, with health care workers (HCWs) being most at risk of COVID-19 infection. A randomized, placebo-controlled, double-blind trial was conducted to assess the effect of the consumption of the probiotic Loigolactobacillus coryniformis K8 CECT 5711 on frontline HCWs exposed to the virus. Parameters related to the incidence and severity of COVID-19 as well as the immune response and the side effects of the COVID-19 vaccine were evaluated. Two hundred fifty-five front-line HCWs aged >20 years were randomized to receive either L. coryniformis K8 or a placebo daily for 2 months. The incidence of SARS-CoV-2 infections was confirmed by PCR or antigen testing. In the volunteers who were vaccinated during the intervention, serum levels of specific IgG were analyzed at the end of the study. The incidence of COVID-19 infection was very low (IR (SD)=0.016 (0.011)), and no significant difference was found between the groups (IRR (95% CI): 1.008 (0.140-7.268), p=0.994). For immune response analysis, the total sample was divided according to the days between the first dose and the antibody analysis (cutoff points were set at <56, 57-80 and >81 days). The specific IgG level decreased over time (p>0.001). However, in the subgroup of subjects for whom more than 81 days had passed since they received the first dose, the specific IgG levels were significantly higher in the subjects that received L. coryniformis K8 (7.12(0.21)) than in the control group (6.48 (0.19)) (P=0.040). Interestingly, the subjects who started probiotic consumption before the first dose reported significantly fewer side effects (of any kind) at the 1st dose of the vaccine (OR: 0.524, p=0.043), specifically less arm pain (OR: 0.467, p=0.017). In conclusion, the administration of L. coryniformis K8 CECT 5711 to HCWs helps to extend the immune protection generated by the COVID-19 vaccine over time.